The function f(x) = 2x - 3

f(x + 1) = 2(x + 1) - 3

=> 2x + 2 -3

=> 2x - 1

f(x - 1) = 2(x - 1) - 3

=> 2x - 2 - 3

=> 2x - 5

g(x) = f(x + 1) + f(x - 1)

=> 2x -1 + 2x - 5

=> 4x - 6

**The required function g(x) = 4x - 6**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now